UMP and General Operations Force (GOF) Southeast Brigade in utilising expertise and innovation - Muhammad Fauzi, Ali (2021)
PEKAN, 25 March 2021 - Universiti Malaysia Pahang (UMP) shares expertise in technology and innovation with the General Operations Force (GOF) Southeast Brigade in creating tools that can help security forces carry out their duties and responsibilities more efficiently.